Revoicing Science: Exploring Didactic Voice-Over With English for Specific Purposes Among Postgraduate Students of Biology - Lertola, Jennifer (Journal of Audiovisual Translation, 2024)
This paper presents a pre-experimental study aimed at investigating the potential benefits of intralingual voice-over (VO) tasks using educational Science videos to enhance speaking skills. The pre-experimental study involved 24 English for Specific Purposes (ESP) postgraduate students of Biology in a blended learning modality over five weeks. Data were collected through speaking pre- and post-tests, a feedback questionnaire and teacher’s observation. The research design of the pre-experimental study was informed by a pilot study planned to explore the potential of intralingual VO tasks using educational Science videos to develop listening and reading skills in a group of 20 ESP postgraduate students of Biology in synchronous online classes over five weeks. The pilot is briefly presented and discussed, as it sets the basis for the current pre-experimental study, which follows a one-group pretest-post-test design, and led to focusing on enhancing speaking skills. Findings of the pre-experimental study support previous research on the beneficial use of VO in the development of speaking skills. These findings encourage further research on didactic VO, especially with similar content videos, to investigate its potential in integrated language skills and ESP-vocabulary acquisition. Lay summary This paper shares the results of a study that looked at whether using voice-over tasks of educational science videos can help students get better at speaking. The study involved 24 Biology postgraduate students in an English for Specific Purposes (ESP) program. The students took part in a mix of online and in-person learning for five weeks. Data were collected by having the students do speaking tests before and after the study, giving them a questionnaire to get their feedback, and having the teacher observe their progress. Before this study, a smaller pilot study was done with 20 Biology postgraduate students in online classes. The pilot helped designing this current study, that uses a design in which a single group of participants is tested before and after a treatment or intervention. The results of this study show that using voice-over tasks can improve speaking skills, supporting what other studies have found. This suggests that using voice-over, especially in videos with similar content, could be useful for improving overall language skills and learning specialized vocabulary.